MR Imaging Features of Acquired Brown Syndrome - Currie, S. (AJNR Am J Neuroradiol, 2009)
Brown syndrome describes the inability of a patient to perform an upward gaze while the eye is adducted due to an abnormality of the superior oblique tendon sheath complex. Use of CT in diagnosing the condition has been reported; however, the use of MR imaging has not. We describe a unique case of Brown syndrome in which the initial CT findings were normal, but MR imaging revealed the abnormality. Key imaging features are illustrated.